2013
DOI: 10.1155/2013/383574
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antioxidant and Isoflavones Concentration in Gamma Irradiated Soybean

Abstract: Serbian soybean genotype Ana was gamma irradiated at doses of 1, 2, 4, and 10 kGy in order to evaluate the influence of gamma irradiation on isoflavone (genistein, daidzein, and their glycosides genistin and daidzin) contents and hydroxyl radical scavenging effect (HRSE). The increase in genistin and daidzin contents as well as antioxidant activities was observed especially at doses of 4 and 10 kGy. Results were also compared with our previous results relating to total phenol content (TPC), DPPH radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…Valjevka, acetone extract). These results are in agreement with the range found in literature (Popović et al, 2013) and within the range previously found for other yellow pigmented soybean seeds (Malenčić et al, 2007.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Valjevka, acetone extract). These results are in agreement with the range found in literature (Popović et al, 2013) and within the range previously found for other yellow pigmented soybean seeds (Malenčić et al, 2007.…”
Section: Resultssupporting
confidence: 94%
“…In particular, the Venera cultivar had the highest TP content, while the Merkur had the lowest. These results are in accordance with the findings of some other authors concerning TP contents in soybean seeds (Malenčić et al, 2007Bellaloui, 2012;Dajanta et al, 2013;Popović et al, 2013). However, some authors detected much higher (Taie et al, 2008) or lower (Mujić et al, 2011) content of TP in tested soybean seeds.…”
Section: Resultssupporting
confidence: 91%
“…Popovic et al. () reported that genistin has a greater activity than other isoflavones and glycosides in FRAP. In this study, FRAP of the four soybean mutant lines was lower than in the original cultivars (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanins were the most important compounds contributing to the antioxidant properties of black soybeans (Zilic et al 2013). FRAP is positively correlated with the total phenolic content and isoflavones (Lee et al 2005, Popovic et al 2013. Popovic et al (2013) reported that genistin has a greater activity than other isoflavones and glycosides in FRAP.…”
mentioning
confidence: 99%
“…These isoflavones are derivatives of daidzin and glycitin. Daidzin is a natural organic isoflavone which is used in prevention of cardiovascular diseases and cancer preventive treatment by scavenging for free radicals (Popovic et al, 2013). Study by Alves et al (2013) to determine antimicrobial activity of phenolic compounds like caffeic and ferulic acid in Pleurotus mushroom species demonstrated antimicrobial activity against some antibioticresistant infections caused by some Gram negative and Gram positive bacteria.…”
Section: Discussionmentioning
confidence: 99%